Cellular and humoral vaccination response under immunotherapies - German consensus on vaccination strategies in neurological autoimmune diseases - Schraad, Muriel Carolyn; Mäurer, Mathias; Salmen, Anke; Ruck, Tobias; Uphaus, Timo; Fleischer, Vinzenz; Luessi, Felix; Protopapa, Maria; Steffen, Falk; Hanuscheck, Nicholas; Pape, Katrin; Brummer, Tobias; et al. (Therapeutic advances in neurological disorders, 2025)
Background: With the development of highly effective disease-modifying treatments, vaccinations are becoming increasingly important in people with neurological autoimmune diseases. However, questions regarding the safety and efficacy of vaccinations under immunotherapy remain. - Objective: To provide recommendations on types and timing of vaccinations for people with neuroimmunological diseases under different immunotherapies. - Design: Our study presents a German evidence-based expert consensus on vaccination under immunotherapies in neurological autoimmune diseases. - Methods: Based on literature research, a consortium of experts evaluated the quality of evidence, integrated clinical experience, and responded to a questionnaire determining an agreement (>75%) on statements concerning vaccination upon immune therapies in neuroimmunological diseases. - Results: The specific humoral and cellular response to vaccination can be compromised under alemtuzumab, azathioprine, cladribine, cyclophosphamide, CD19/CD20 antibodies (inebilizumab, ocrelizumab, ofatumumab, rituximab, ublituximab), dimethyl fumarate/diroximel fumarate, FcRn inhibitors (efgartigimod, rozanolixizumab), complement C5 inhibitors (eculizumab, ravulizumab, zilucoplan), interleukin-6 receptor antibodies (tocilizumab, satralizumab), intravenous immunoglobulins, long-term steroid administration, methotrexate, mitoxantrone, mycophenolate mofetil, tacrolimus, teriflunomide, tumor necrosis factor-α blockers, and sphingosine-1-phosphate receptor modulators (fingolimod, ozanimod, ponesimod, siponimod), as well as after autologous stem cell transplantation. The lymphocyte count can have an influence here. Overall, it is generally advisable to complete vaccination before starting immunotherapy. However, in the case of an active inflammatory disease course with possible irreversible neurological deficits, a delay in therapy initiation until immunization has been completed cannot be justified. The application of live vaccines is contraindicated for most therapies and is only recommended after a strict risk-benefit assessment. - Conclusion: Vaccinations are necessary for individuals on immunotherapy to reduce the risk of infections and the associated risk of worsening neurological autoimmune diseases. However, the humoral and cellular vaccination response may be impaired under immunotherapy necessitating close monitoring. Here, we provide applicable recommendations to optimize immunization for individuals receiving immunotherapy due to a neurological autoimmune disease.